From the edge to the heart: Female employment in 19th-century Italy - Giuliana Freschi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2023)
Women have long been at the edge of economic history. According to Humphries (1991) and Sharpe (1995), shifting them from there ''to the heart'' goes into stages. The first stage involves recognising the extent to which the role of women has been neglected. The second stage aims to integrate women in the mainstream of economic history, with potentially revolutionary results. As stated in the introduction of the present book, the methodological challenge lies in proving that it is possible to uncover the economic culture not only in womenâ exteuro™s writings, as many did not leave behind written records, but also in their actions. Therefore, this book goes beyond the scope of Humphries and Sharpe by placing women not only at the core of economic history but also at the centre of the economic culture of their times. The initial part of the book focuses on women who have left traces of their economic thought, not through their writings, but through their extraordinary experiences. It explores the stories of women in business, female entrepreneurs, and their untold or forgotten narratives. The follwing sections of the book will delve into the role of women in education, politics, and economics. These sections rely on sources that have not been traditionally used to study women's work, such as correspondence or unprinted material, to reconstruct the intellectual history of women who contributed to the history of economics and the economy. This portion of the book delves into debates and patterns regarding women in the labour market, utilising often overlooked sources. The present chapter reflects on the significance of re-evaluating the role of ordinary, ''everyday'' women's work in the economic development of countries (Bateman 2019). It contributes to the ongoing discussion on female labour force participation in the past and concludes that when work was available, women worked. In the applications for poor relief in the city of Florence between 1810 and 1812, families had to describe the occupational status of all their members. Hence, the applications represent a valuable source to explore female work. For instance, Maddalena and Elisabetta worked with silk when they ''had it'' or when they ''could''. The 26-year-old daughter of one of the households requesting the poor relief, bleached ''when she found it'', while her younger sister was engaged in a ''little job'' (il lavorino). Thus, it aligns with a strand of the debate that emphasises the importance of demand factors, rather than supply factors, in determining women's employment in historical perspective. However, providing new estimates of female employment in the past is outside the scope of this chapter. The main contribution is that, alongside with demand factors, also cultural ideology had a pivotal role. Thus, I focus on the tendency of women to report their occupation, and how the reporting patterns varied over time, across locations, and social classes.
Keywords: B54; J16; J2; J62; 330; Italy; Labour; Gender; Feminist Economics